Regioselective Palladium(0)-Catalyzed Cross-Coupling Reactions of 5,7-Dichloro-1,6-naphthyridine - Ali, Iftikhar; Hassan, Zahid; Hein, Martin; Falodun, Abiodun; Patonay, Tamás; Villinger, Alexander; Langer, Peter (Synthesis, 2012)
A variety of mono- and diarylated naphthyridine derivatives were prepared by site-selective Suzuki–Miyaura cross-coupling reactions of 5,7-dichloro-1,6-naphthyridine. The first attack occurs at position 5.
Keywords: catalysis; palladium; Suzuki reaction; naphthyridine; regioselectivity